2014
DOI: 10.1002/adsc.201301004
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)‐Catalyzed Decarboxylative Heck Arylations of Acyclic Electron‐Rich Olefins with Internal Selectivity

Abstract: Despite the recent emergence of decarboxylative CC bond forming reactions, methodologies providing internally arylated electron‐rich olefins are still lacking. We herein report on palladium(II)‐catalyzed decarboxylative Heck arylations of linear electron‐rich olefins with excellent selectivity for the internal position. The method allows a variety of electron‐rich linear olefins to undergo arylation with ortho‐functionalized aromatic carboxylic acids, including heterocycles. The reaction mechanism has been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…44 Although the protonation step is effectively performed by the aromatic carboxylic acids, stoichiometric decarboxylative coupling of 2,6-dimethoxybenzoic acid with styrene could be observed, selectively yielding 1,3-dimethoxy-2-(1-phenylvinyl)benzene (Scheme 6). This rather exclusive 45 regioselectivity to 1,1-disubstituted olefins is likely caused by the steric bulk of the ligand's N-aryl moiety, forcing styrene coordination in a manner only allowing a 2,1-insertion mechanism.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…44 Although the protonation step is effectively performed by the aromatic carboxylic acids, stoichiometric decarboxylative coupling of 2,6-dimethoxybenzoic acid with styrene could be observed, selectively yielding 1,3-dimethoxy-2-(1-phenylvinyl)benzene (Scheme 6). This rather exclusive 45 regioselectivity to 1,1-disubstituted olefins is likely caused by the steric bulk of the ligand's N-aryl moiety, forcing styrene coordination in a manner only allowing a 2,1-insertion mechanism.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a contemporaneous study, Larhed and co-workers demonstrated that electron-rich alkenes, enamides, and enol ethers, can undergo a similar decarboxylative Heck reaction using benzoquinone (BQ) as the stoichiometric oxidant (Scheme 9C). 64 The reaction was expanded to 1,1-disubstituted vinylphosphonates by Yao and co-workers (Scheme 9D). 65 The reaction gave the kinetically favored E isomer over the thermodynamically favored Z isomer in DMSO/DMF (consistent with Scheme 8).…”
Section: Scheme 7 Decarboxylative Heck Reactions With O 2 As An Oxidantmentioning
confidence: 99%
“…Throughout the years, we have investigated various aryl palladium precursors such as aryl boronic acids, , aryltrifluoroborates, , and more recently benzoic acids for Pd(II)-catalyzed Heck arylations and synthesis of aryl amidines and aryl ketones . Although aryl carboxylic acids may undergo decarboxylation to form an aryl palladium complex, the use of aryl carboxylic acids for palladium-catalyzed decarboxylative coupling reactions is limited to electron-rich, sterically congested ortho -substituted substrates or the use of a Cu decarboxylative cocatalyst. ,, The limitations of Pd(II)-catalyzed decarboxylative coupling reactions prompted us to investigate alternative aryl palladium precursors.…”
Section: Introductionmentioning
confidence: 99%